Erasing Diversity: Mediating Class, Place, Gender and Race in The Moorside. Issue 1 (January 2020) - Forrest, David; Johnson, Beth
Abstract : This article is focused on the 2017 BBC drama, The Moorside . Over two episodes, it revisits the events surrounding the 'disappearance' of Shannon Matthews, a nine-year-old schoolgirl from Dewsbury in West Yorkshire, with the drama culminating in the arrest of Shannon's mother, Karen, on charges of child neglect and perverting the course of justice. We identify the events depicted in The Moorside and, in particular, the media's framing of them, as central to the formation of pervasive and corrosive narratives of 'broken Britain'. In revisiting the Matthews case, The Moorside re-animates and, we argue here, further perpetuates these discourses by rendering them through highly constructed and reductive frameworks of class, place, gender and race. Our analysis considers the textual strategies at work in the drama, some of its key intertexts, questions of diversity – in class terms – within the BBC, and the role of Sheridan Smith, The Moorside 's 'star', as a conduit for narratives of regional and social identity.